Digital Transformation in Indonesian Agriculture: Enhancing Supply Chain Performance in the Era of Smart Farming 2025 - Fauzi, Moh. Rifqi (Journal of Economics and Social Sciences (JESS), 2025)
Digital transformation has become a strategic mechanism to address persistent inefficiencies in agricultural supply chains, particularly those related to logistical delays, supply–demand imbalances, and lack of data transparency. This study investigates the impact of digital technologies on the performance of agricultural supply chains in Indonesia within the framework of Smart Farming 2025. Using a qualitative approach with a library research method, this research analyzes various scholarly sources, including national and international journals, policy papers, and institutional publications. The findings reveal that digital transformation enhances logistics efficiency, improves demand forecasting, strengthens product traceability, and increases farmers’ access to markets and technologies. Despite these advantages, challenges remain—particularly the digital divide, infrastructural limitations, and resistance to technology adoption. Therefore, this study highlights the need for collaborative strategies among governments, private sectors, and farming communities to build an inclusive, adaptive, and sustainable digital agriculture ecosystem.